Post-traumatic cognitive disorders: the cholinergic therapy options - O. S. Levin; A. Yu. Nikitina (Klinicist)
Traumatic brain injury (TBI) is one of the most common causes of neurological disability in young and middle-aged people. Cognitive impairment is the most persistent and universal brain injury syndrome in cases of TBI and, moreover, the best indicator of TBI severity to predict its outcome. Cognitive impairment can persist persistently even after mild TBI, which accounts for 70–90 % of the total number of trauma patients. This may be due to the fact that in cases of mild TBI, the most fragile functions of integrative structures of the frontal and temporal lobes are slowly and not always completely recovered and the dominant clinical manifestation become complex neuropsychological disorders. Individuals with repeated mild TBI are characterized by development of chronic post-traumatic encephalopathy, that is a kind of neurodegenerative disease manifested by slowly increasing cognitive impairment, parkinsonism and a number of other neurological syndromes. Early detection and adequate correction of the cognitive impairments may improve the outcome of injury of diverging severity. Due to the fact that the pathogenesis of TBI is based on disorder of cholinergic system, the patients have predominance of regulatory disorders in the neuropsychological profile, as well as a combination of cognitive and affective disorders. Administration of acetylcholine precursors leads to rapid increase of free choline levels in plasma that penetrates the blood-brain barrier well and enhances cholinergic activity by increasing acetylcholine synthesis and release. The article considers the possibilities of using acetylcholine precursors in connection with their potential to block the progressive impairment of cognitive functions induced by trauma as well as to reduce severity of behavioral and affective disorders.